Kingella Kingae Sequence Type-Complex 14 Arthritis in a 16-Month-Old Child in Greece. Issue 1 (January 2015) - Grivea, Ioanna N.; Michoula, Aspasia N.; Basmaci, Romain; Dailiana, Zoe H.; Tsimitselis, George; Bonacorsi, Stéphane; Syrogiannopoulos, George A.
Abstract : We describe the first case of Kingella kingae arthritis in a 16-month-old girl in Greece, which has been diagnosed by novel molecular techniques. A joint aspiration of her knee was performed before the initiation of antibiotics, as well as on the 5th and 14th day of empiric antimicrobial therapy. The synovial fluid white blood cell count decreased from 65, 000 to 1500 cells/mm 3, but the percentage of neutrophils remained 90% in all 3 specimens. Molecular analysis of the synovial fluid specimens by real-time polymerase chain reaction and multilocus sequence typing enabled us to reveal the presence of K. kingae belonging to the international sequence type-complex 14, which persisted up to the fifth day of antibiotic therapy. Abstract : Supplemental Digital Content is available in the text.